2021
DOI: 10.2196/30239
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Directly Supervised Telehealth-Based Exercise Training Program in Patients With Nonalcoholic Steatohepatitis: Feasibility Study

Abstract: Background Most patients with nonalcoholic fatty liver disease (NAFLD) are physically inactive despite the well-known benefits of physical activity. Telehealth offers promise as a novel way to deliver an exercise training program and increase physical activity. However, the feasibility, safety, and efficacy of telehealth-based exercise programs is unknown in patients with NAFLD. Objective The aim of this study was to determine the feasibility of a direc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 7 publications
2
32
0
Order By: Relevance
“…Studies to determine role of telehealth specifically for NAFLD/NASH patients remain few and far between 16,17 . But opportunities abound for the use of telehealth to improve diagnosis and management of fatty liver disease.…”
Section: Applying Telehealth In Diagnosis and Management Of Nafld/nashmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies to determine role of telehealth specifically for NAFLD/NASH patients remain few and far between 16,17 . But opportunities abound for the use of telehealth to improve diagnosis and management of fatty liver disease.…”
Section: Applying Telehealth In Diagnosis and Management Of Nafld/nashmentioning
confidence: 99%
“…Using wearable devices can help monitor simple measures such as step count, daily weights and even diet. Motz et al demonstrated improvements in physical, laboratory, and imaging findings of 3 NASH patients by applying telemonitoring and supervised exercise training 17 …”
Section: Applying Telehealth In Diagnosis and Management Of Nafld/nashmentioning
confidence: 99%
See 3 more Smart Citations